Co-pyrolysis characteristics of municipal sewage sludge and hazelnut shell by TG-DTG-MS and residue analysis. (April 2017) - Xu, Xinyang; Zhao, Bing; Sun, Manli; Chen, Xi; Zhang, Mingchuan; Li, Haibo; Xu, Shucong
Abstract: Co-pyrolysis characteristics of municipal sewage sludge and hazelnut shell blend have been studied in this work. The behavior of co-pyrolysis was researched by a method of multi-heating rates and different blend ratios to analyze thermal decomposition stages. The experimental data of the blended samples in TG-DTG plots were compared with calculated data to investigate the interactions during co-pyrolysis. The bio-chars investigated by SEM and FTIR spectra were used to examine the physical and chemical changes. The results showed there are four thermal decomposition stages during co-pyrolysis, with hydrocarbon transforming to gas evolution in the second and the third stages. The inhibitive interaction occurred between 260 and 400 °C and the accelerative interaction occurred between 450 and 900 °C during co-pyrolysis. The activation energy of the blended sample was 51.97–178.84 kJ/mol in the second stage and 207.04–630.73 kJ/mol in the third stage calculated by DAEM.